Optical properties of nanostructured metallic systems : Studied with the finite-difference time-domain method - Rodrigo, Sergio G. (Springer Theses, 2012)
The common belief is that light is completely reflected by metals. In reality they also exhibit an amazing property that is not so widely known: under some conditions light flows along a metallic surface as if it were glued to it. Physical phenomena related to these light waves, which are called Surface Plasmon Polaritons (SPP), have given rise to the research field of plasmonics. This thesis explores four interesting topics within plasmonics: extraordinary optical transmission,  negative refractive index metamaterials, plasmonic devices for controlling SPPs, and field enhancement phenomena near metal nanoparticles.